Solve by substitution-7x-2y=11X-2y=11
The other answers are good, but I'll offer another approach and simplify y.
1. Solve for x
All 3 expressions are on the same line, so you have a major clue. Notice a pattern or similarity between two of the expressions?
There's a -2y in the first and second expression. This means the x term doesn't change the value of the expression!
So, x must be zero (x = 0)
2. Solve for y
Since x=0, we're left with -2y = 11
Divide 11 by -2, and you have -11/2
Remember to simplify! Many teachers take off points for leaving an improper fraction. Divide 11 by -2 and you have five and a half (5.5 or 5 1/2)
Hope this help you, Maddie!
Both of the polynomial pieces must be equal to 11. Thus -7x-2y = 11 and 11x - 2y = 11.
Solve the second equation for -2y by subtracting 11 x from both sides and you have -2y =11+11x
Substitute this into the first equation where the -2y is and you have -7x + 11 + 11x = 11.
Combine terms to have 11 + 4x = 11
Subtract 11 from both sides and have 4x = 0 or x = 0
Substitute this into either original equation to solve for y. In either case -2y = 11 or and y = -11/2.